Educational interventions and back pain in a Health Unit: an experience report (Research, Society and Development, 2021)
To report the academic experience in educational interventions related to low back pain at the Três Barras health unit. This is a qualitative study, of the experience report type, reporting actions developed at the Três Barras Health Unit in the municipality of Agrolândia in Santa Catarina, in the months of July and August 2020, with patients who reported complaints of low back pain. The performance of self-care practices such as physical activities, stretching and dietary re-education form habits that have reduced the prevalence of back pain. All those who made a lifestyle reform adhering to a diet of whole foods, increasing consumption of fruits and vegetables, increasing water intake, as well as integrating light physical activities and stretching, obtained relief from low back pain with a significant reduction in the complaint. They reduced the demand for primary and specialized care, requested less medical certificate and used fewer medications. Some factors that aggravate the instabilities of the lumbar spine can be managed by the user, thus bringing partial or complete relief from the condition. Educational intervention with a focus on proactive actions is of vital importance in the management of these patients, as they can form habits that reduce the prevalence of low back pain, thus reducing care for this complaint.